A formação dos professores na educação especial de Toledo-PR. - Santi, Ana Paula (2018)
This research, on teachers’ training in special education, concerns the educational historiography and has as general objective to present and discuss fundamental aspects on teachers’ training policies in the area of Special Education in the municipality of Toledo-PR. We highlight the main changes in the educational modality from the 1990s, at national and local levels, underlining the apogee of the Special Education policy, from the perspective of inclusive education. Therefore, we made use of documentary analysis and reference bibliographies in the subject, constituting a historical framework of social-educational policies in different areas of the educational system regarding the theme. These elements involved the set-up of the Special Education history in the municipality of Toledo, especially as regards the distinction experienced in the policies and the characteristics of teachers’ training who began to work with students with disabilities in regular education in the early years of Primary School of the municipal school system. The study found that most of the teachers working with this public obtained their training starting in the 1990s in lato sensu postgraduate courses offered in the western region of Paraná by private institutions. These results show the direction of public policies for teacher training in the sense of a considerable reorganization towards meritocracy, as well as the large exploitation of the market in this educational sphere. The results of the research have demonstrated the material relations of the social organization that determine the direction of teachers’ training policy in the area of the Special Education, which refers, ultimately, to the genesis of the inequality/marginality/exclusion of the person with or without disabilities in society. The research points out directive elements of continuing education of teachers' technical and political educational development as contributory factors for the ability to explain the social contradictions that mark the trajectory of humanity.